The Influence of Employer Branding on Intention to Apply, mediated by Organization Reputation and Person-Organization Fit in Generation Z Talent Candidates - Jordan, Muhammad Hazel; Desiana, Putri Mega (Syntax Literate, 2024)
This study aims to examine how employer branding influences intention to apply among potential Generation Z candidates. In practice, research related to employer branding has not been common and studied in more depth, especially on potential Generation Z talent candidates, therefore this study seeks to fill the gap in previous academic literature examining similar topics, In addition, this study also seeks to examine the mediating role of organization reputation and person-organization fit in the influence of employer branding on intention to apply. The sample in this study consisted of 251 final year students and fresh graduates from 10 top universities in Indonesia. Mediation analysis was conducted using structural equation modeling. The findings of this study show that the relationship between employer branding and intention to apply is positive and significant. In addition, empirical evidence also shows the role of organization reputation in increasing the influence of employer branding dimensions on intention to apply. In addition, the results show that organization reputation partially mediates the effect of employer branding on intention to apply, which emphasizes the need to align the dimensions of employer branding with organization reputation in strengthening its effect on intention to apply. Employer branding is important to be a current and future investment priority for employer companies that enable companies to attract top talent, improve organizational reputation and help companies achieve a better position in the job market.